Erik’s Oppression in Gaston Leroux’s The Phantom of the Opera - ALIFA RUKMI HIDAYANTI C. P. (LITERA KULTURA : Journal of Literary and Cultural Studies, 2015)
Abstract Erik’s oppression is the main focus of this study in Gaston Leroux’s novel entitled The Phantom of the Opera. This study applies descriptive analysis method. The main data is taken from the novel written by Gaston Leroux entitled The Phantom of the Opera. This thesis is purposed to analyze how the depiction of Erik’s oppression, also give the analysis of the factors and also the impacts of Erik’s oppression, that is already stated in the statement of the problem. Oppression is arbitrary thing that someone do to the minorities who does not have power to against it. The concept of oppression, refers to the unjust use of power. This study applies the concept of oppression and the theory of power and oppression by several expert, such Peg O’Connor and Elizabeth D.Hutchison. The theories and concept are well applied to reveal the statement of the problem. The analysis points out that Erik has pictured the image of oppression which dominate in this novel. Erik with his power dominate and oppress the others by giving some rules in Paris Opera, such the manager have to pay some money to him. It is because Erik with his great expertise feels has a higher power than others. This oppression made people surround him depressed and made them submissive by his power. However oppression can definitely lead to something that is not fair. Supervision and control themselves may be also avoid that action. Key Words : oppression, power Abstrak Penindasan Erik adalah fokus utama dari studi ini dalam novel Gaston Leroux berjudul The Phantom of the Opera. Penelitian ini menggunakan metode analisis deskriptif. Data utama diambil dari novel yang ditulis oleh Gaston Leroux berjudul The Phantom of the Opera. Skripsi ini bertujuan untuk menganalisa bagaimana gambaran dari penindasan Erik, serta memberikan analisis mengenai faktor dan dampak dari penindasan Erik, yang telah disebutkan dalam rumusan masalah. Penindasan adalah tindakan sewenang-wenang yang seseorang lakukan kepada minoritas atau seseorang yang tidak memiliki kekuatan untuk melawan. Konsep dari penindasan, mengacu pada ketidakadilan dari penggunaan suatu kekuasaan. Skripsi ini menggunakan konsep penindasan dan teori kekuasaan dan penindasan oleh beberapa ahli, seperti Peg O’Connor dan Elizabeth D.Hutchison. Teori dan konsep diterapkan dengan baik untuk mengungkapkan permasalahan yang ada. Analisis juga menunjukkan bahwa Erik telah digambarkan sebagai citra penindasan yang mendominasi dalam novel ini. Erik dengan kekuasaannya, mendominasi dan menindas yang lain dengan memberikan berbagai peraturan di Opera Paris, seperti sang manajer harus membayarkan sejumlah uang kepadanya. Hal ini disebabkan karena Erik dengan kemampuannya yang luar biasa, merasa memiliki kuasa yang lebih tinggi daripada yang lain. Hal ini membuat orang-orang di sekitarnya tertekan dan membuat mereka tunduk dalam kekuatannya. Bagaimanapun penindasan pasti mengarah pada sesuatu yang tidak adil. Pengawasan dan pengontrolan mungkin bisa menghindarkan dari tindakan tersebut. Kata Kunci: penindasan, kekuasaan INTRODUCTION The Phantom of the Opera is a classic epic literary work. It starts from the author, Gaston Leroux. Before Gaston Leroux died, there's even a nine films were made based on the adaptation of his novels. Because of his merit in the field of journalism, Gaston Leroux has earned a legion nobility. 1907 is an important year for Gaston Leroux, the year where he quit being journalist and his book Le mystere de la chambre jaune success in the market. Then the next year also promote his continuation sequels. Gaston Leroux regarded as the successor of Alexandre Dumas, and known as the king of fiction writers. The phantom of the opera is a classic work that has often been adapted into many work such film, since it was first published in 1910 in France. Probably from the many adaptation versions of The Phantom of the Opera, which is considered closest to the original version Leroux's novel itself is a Hollywood adaptation, starring by Lon Chaney and directed by Rupert Julian in 1925. In 1907, Gaston had published Le Mystere de la chambre jaune , which was a great success and was praised by Agatha Christie. The most famous novel was Le Fantome de l' Opera that has been translated into various languages and the movies was made. Andrew Lloyd Weber pick that story in a musical drama in 1986. The Phantom of the Opera has been translated in English, Norwegian, Czech, Hebrew, German, Denmark, and Japan. Has been noted that approximately 18 million people have watched the drama works of Andrew Lloyd Weber's, and the following sequel is 'Love Never Dies'. This novel has been repeatedly adapted to the various series on television, radio, and stage plays. Has been noted that there are about twenty-five versions of the movies. Many authors who write the sequel of this story based on this text. Even the story of the Phantom of the Opera is available and can be downloaded from playstore and is also available in the windows store. It is proved that this novel is an epic literary work and deserve to be the pride of the world heritage. Phantom of the Opera no longer owned by the French, but it has become the world's cultural heritage. This story is about the great misfortune which can come to someone when they are different from everyone else, and when that person is not accepted for who they are. When people do not look into the heart but look at appearances only, they quickly misjudge that person. This is what happens to Erik, in spite of his enormous musical talent, his skillfulness as a magician, architect, and inventor; he cannot join the human race because of his terrible face. He wants nothing more than acceptance, especially acceptance from a woman. He wants a wife and a normal life in a normal house like other people. He will never have these things and he knows it. He becomes revengeful and he oppress those people so that all he wishes comes true. He uses his genius to create a mysterious world where he can oppress people. Therefore it is very interesting to describe how the depiction of the Erik oppression, what factors cause Erik oppression, and what